Extracting Ocean Colour and Sea-grass Information from Remote Sensing Data: Opportunities and Limitations - Hashim , Mazlan; Abdullah, Adeli; Rasib, Abd. Wahid (2000)
The opportunities and limitations of extracting ocean colour and sea-grass information based on studies carried out at UTM Centre for Remote Sensing were identified in this study. The Landsat-5 Thematic Mapper â„¢ data were used in two selected test sites: (i) off Kuala Terengganu including all island gazetted as Marine Park, and (ii) off Kuala Kedah including Pulau Langkawi and nearby small islands. Phytoplankton information were extracted based on regressing samples of phytoplankton density collected at the time of satellite over-pass of the corresponding test areas with the reflectance values recorded by the satelliteâ€™s sensor while information on sea-grass were determined using substrate indices computed from the measured reflectance of the sea area.